2010
DOI: 10.1158/1078-0432.ccr-09-2084
|View full text |Cite|
|
Sign up to set email alerts
|

Development of Molecularly Targeted Therapies in Hepatocellular Carcinoma: Where Do We Go Now?

Abstract: Hepatocellular carcinoma (HCC), once considered an orphan disease in the West, has become a global health concern. It is the third leading cause of cancer death worldwide, and its incidence continues to increase. Historically, the development of new systemic agents for advanced HCC has been lacking despite no clear benefit with traditional cytotoxic therapies. Although two randomized studies with sorafenib for the treatment of HCC patients have recently been completed, survival benefits have been modest and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 84 publications
(78 reference statements)
0
75
0
Order By: Relevance
“…Only 15% are eligible for curative treatment [1] . The 2 year recurrence rate can reach up to 50%, even for patients undergoing surgery, with a 10 year rate of 76% [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Only 15% are eligible for curative treatment [1] . The 2 year recurrence rate can reach up to 50%, even for patients undergoing surgery, with a 10 year rate of 76% [2] .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to HCC, the only systemic agent that has been shown to improve survival is sorafenib, an oral multikinase inhibitor (5,6). Beyond sorafenib, several studies are evaluating novel combinations (9), and although benefits have been observed with sorafenib, other single agents (e.g., sunitinib) have not shown efficacy in HCC (10).…”
Section: Introductionmentioning
confidence: 99%
“…Only 15-30% of patients present in early stage HCC and can receive curative treatments [4]. This is mainly due to liver cirrhosis associated with hepatocarcinoma, and the late presentation reported in most patients.…”
Section: Early Stage Hccmentioning
confidence: 99%